Gamma Knife Neurosurgery - Ganz, Jeremy C.; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2011)
Today, over 500,000 patients have been treated world wide in 250 Gamma Knife Centres in 37 countries each one treating between 150 and 700 patients a year. The current book serves as a textbook, training manual and reference book for those involved in Gamma Knife practice covering the theoretical background, the practical aspects of treatment, the social side of the method and necessary information not only for users but for those who refer to the Gamma Knife. It also covers some aspects of the hospital and social administration required for optimal use of the technology, also looking at the effect of the internet on specialist medical practice.It also presents the completely new Gamma Knife (Perfexion), a new technology which extends the range of the Gamma Knife and will be the treatment standard for the future
Section 1 -- Background Principles and Technical Development -- 1 - Introduction and the Nature of Radiosurgery -- 2 - Principles of Stereotaxy -- 3 - Ionising Radiation and its Effects on Living Tissue -- 4 - Biological Effects of Ionising Radiation -- 5 - Ionising Radiation and Clinical Practic -- 6 - Gamma Knife Development from 1967 to 2010 -- 7. Radiophysics, Radiobiology and the Gamma Knife -- 8 - Preparation for Treatment Planning -- 9 - Dose plan Indices -- Section 2 -- The Patient$1 (Bs Experience -- 10 - Gamma Knife surgery and computer networks -- 11 - Aims of Gamma Knife Surgery -- 12 - Principles of Information and Follow Up -- Section 3 -- The Gamma Knife and Specific Diseases -- Tumours -- 13 - Vestibular Schwannomas -- 14 - Meningiomas -- 15 - Gamma Knife for Cerebral Metastases -- 16 - Intraparenchymal Intrinsic Brain Tumours -- 17 - Tumours of the Pituitary Region -- 18 - Less Common Skull Base Tumours.- -- Section 3 -- The Gamma Knife and Specific Diseases -- Vascular Diseases -- 19 - Gamma Knife for Cerebral Vascular Anomalies -- Section 3 -- The Gamma Knife and Specific Diseases -- Functional Indications -- 20 - Trigeminal Neuralgia -- 21 - Diverse Functional Indications -- Section 3 -- The Gamma Knife and Specific Diseases -- Less Common Indications -- 22 - Rare tumours and other lesions -- 23 - Orbital Indications -- Section 4 -- Conclusions -- 24 - Conclusion and possible Future Trends -- Appendix - Simple Unassisted Frame Application -- Index.s
Keywords: Medicine; Neurosurgery; Medicine & Public Health; Neurosurgery